2018
DOI: 10.1016/j.talanta.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct solid phase microextraction combined with gas chromatography – Mass spectrometry for the determination of biogenic amines in wine

Abstract: A direct method based on immersion solid phase microextraction (DI-SPME) gas chromatography mass-spectrometry (GC-MS) was optimized and validated for the determination of 16 biogenic amines in Polish wines. In the analysis two internal standards were used: 1,7-diaminoheptane and bis-3-aminopropylamine. The method allows for simultaneous extraction and derivatization, providing a simple and fast mode of extraction and enrichment. Different parameters which affect the extraction procedure were studied and optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…The total content for these five BA was high, therefore the amount of soy sauce used in cooking or consuming needs to be treated with concern. Papageorgiou, Lambropoulou, Morrison, Namieśnik, and Płotka‐Wasylka (2018) tested 38 samples of red wine and found that with the maximum level of total amines of 31.5 mg/L, and concluded that the concentration of BA in red wines were below the levels that would cause adverse effects on consumers. All eight BA were determined in 13 species of freshly‐caught fish in China.…”
Section: Introductionmentioning
confidence: 99%
“…The total content for these five BA was high, therefore the amount of soy sauce used in cooking or consuming needs to be treated with concern. Papageorgiou, Lambropoulou, Morrison, Namieśnik, and Płotka‐Wasylka (2018) tested 38 samples of red wine and found that with the maximum level of total amines of 31.5 mg/L, and concluded that the concentration of BA in red wines were below the levels that would cause adverse effects on consumers. All eight BA were determined in 13 species of freshly‐caught fish in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of MS/MS is very expensive and takes too much time in preparing the sample before analysis [67]. Nevertheless, the use of derivatization agents comes with the following issues: loss of the analytes; occurrence of byproducts; extension of sample preparation time; and potentially longer process [75]. Acylation reagents have become an alternative to silylation reagents for their capability to decrease the polarity of amine, which aids in decreasing nonspecific adsorption effects and modifying GC properties.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…Successful biogenic amine analysis has also been reported using GC coupled with mass spectrometry (GC-MS) [74,76]. Besides these derivatizing reagents, Papageorgiou et al [75] also introduced the use of isobutyl chloroformate (IBCF) to successfully derivatize the structure of amines, as shown in Figure 3.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…The obtained LODs were 20-250 μg kg −1 . On the whole, due to the considerable sensitivity and the specific structural information for the derivatized amines that MS or MS/MS detectors can provide, they are the most efficient detection tools for metabolites which are usually present in low concentrations [55]. Furthermore, they are very helpful in identifying co-eluting peaks in real sample analysis.…”
Section: Chromatographicmentioning
confidence: 99%